Manajemen Risiko Lembaga Pendidikan dalam Pesrpektif Al-Qur’an Surat Yusuf: 43-49 - Dila Nurlaila Zannah; Cecep Anwar (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2022)
As long as time goes on, risk will always be present accompanying human life and all its affairs. Educational institutions as one of the human affairs must have various risks from each component of education. The management process of educational institutions must be based on the applicable legal basis, namely the Qur'an as a Muslim's life guide and laws regulations of the country. This article aims to describe the risk management of educational institutions in the perspective of the Qur'an. A qualitative approach using the literature study method is an option in the preparation of articles so as to find some findings that can be implemented by a Muslim manager in the risk management of the educational institution he carries. Risk management is a logical and systematic method in the process of identifying, quantifying, determining attitudes and policies, determining solutions, as well as monitoring the evaluation of supervision and reporting of risks that take place in every activity or organizational process. Risk management in educational institutions means managing risk in every component of education including educational objectives, curriculum, teaching and educational staff, students and media or educational infrastructure. Keywords: Risk Management, Educational Institutions, Al-Qur'an Perspective Selama waktu terus berjalan, risiko akan selalu hadir mengiringi kehidupan manusia dan segala urusannya. Lembaga pendidikan sebagai salah satu urusan manusia pasti memiliki risiko yang beragam dari setiap komponen pendidikan. Proses manajemen lembaga pendidikan harus berlandaskan dasar hukum yang berlaku yaitu al-qur’an sebagai pedoman hidup seorang muslim serta perundang-undangan aturan dari negara. Artikel ini bertujuan memaparkan bagaimana manajemen risiko lembaga pendidikan dalam perspektif al-qur’an. Pendekatan kualitatif menggunakan metode studi pustaka menjadi pilihan dalam penyusunan artikel sehingga menemukan beberapa temuan yang bisa dilaksanakan seorang manajer muslim dalam manajemen risiko lembaga pendidikan yang diembannya. Manajemen risiko merupakan metode logis dan sistematik dalam proses identifikasi, kuantifikasi, menentukan sikap dan kebijakan, menetapkan solusi, serta melakukan monitor evaluasi supervisi dan pelaporan risiko yang berlangsung pada setiap aktifitas atau proses organisasi. Manajemen risiko dalam lembaga pendidikan berarti mengelola risiko pada setiap komponen pendidikan memuat tujuan pendidikan, kurikulum, tenaga pendidik dan kependidikan, peserta didik dan media atau sarana prasaran pendidikan. KataKunci:Manajemen Risiko, Lembaga Penididikan, Pesrpektif Al-Qur’an